FRI0293 Imbalance in circulating subsets of innate lymphoid cells is linked to disease activity and type i interferon signature in primary sjÖgren's syndrome. (12th June 2018) - Blokland, S.L.; van den Hoogen, L.L.; Leijten, E.F.; Kruize, A.A.; Radstake, T.R.; van Roon, J.A.
Abstract : Background: Recent studies indicate an important role for innate lymphoid cells (ILCs) in the pathophysiology of rheumatic diseases. In rheumatoid arthritis and spondyloarthropathies elevated numbers of subsets of ILCs have been found at the site of inflammation producing cytokines including IFN-γ and IL-22 and in addition, group 3 ILC have been suggested to be involved in formation of ectopic lymphoid structures in rheumatic diseases, Shikhagaie Nat Rev Rheumatol 2017 Wenink A and R 2017). ILC3-like cells producing IL-22 have been found in the salivary glands of pSS patients. Ciccia ARD 2012 However, circulating ILC have not yet been studied in primary Sjögren's syndrome (pSS) and systemic lupus erythematosus (SLE). Furthermore, SLE and pSS are characterised by presence of a type I interferon (IFN) signature in a large proportion of the patients. Animal studies in HIV and asthma implicate type I IFN, produced by plasmacytoid dendritic cells (pDCs), to regulate the survival of group 2 and group 3 ILCs (ILC2 and ILC3) via increase of Fas (CD95) expression, rendering the ILC more susceptible to apoptosis, Maazi JACI 2017, Zhang JCI 2015. Duerr Nat Immunol 2016 Objectives: In this study, we explored for the first time the frequency and phenotype of circulating ILCs in pSS and SLE and their relation to the IFN signature. Methods: Frequencies and phenotypes of ILC subsets and pDCs were assessed by flow cytometry in peripheral blood of patients with pSS (n=20), SLE (n=20) and healthy controls (n=17). Patients were stratified by the presence or absence of an IFN signature as assessed by RT-qPCR on peripheral blood mononuclear cells as previously described. Brkic ARD 2013 Results: Results ILC1 numbers were increased in peripheral blood of patients with SLE as compared to healthy controls and in pSS patients ILC1 numbers correlated with disease activity (ESSDAI score), serum IgG levels and anti-SSB autoantibodies (all p<0.05). Numbers of ILC1, ILC2 or ILC3 did not significantly differ between patients with SLE and pSS. However, patients with a high expression of the type I IFN signature had significantly decreased numbers of ILC2 and ILC3 (p=0.04 and p=0.02, respectively). The decrease of ILC2s and ILC3s was related to increased expression of Fas (CD95) on these cells in patients with a high type I IFN signature (both p=0.01). Conclusions: Both in SLE and pSS, a type I IFN signature is related to reduced numbers of circulating ILC2s and ILC3s in association with increased Fas expression on these cells possibly rendering them more susceptible to Fas/FasL-dependent apoptosis at peripheral sites. Disclosure of Interest: None declared